Restrukturisasi Perusahaan Yang Mengalami Financial Distress Melalui Merger - Sylvina Anggita; Sunarmi Sunarmi; Tengku Keizerina Devi Azwar; Detania Sukarja (Universitas Sains dan Teknologi Komputer, 2023)
The company's survival efforts or strategy must be to restructure the company through mergers which can give the company a large market share, increase working capital, increase workforce, and obtain technological capabilities which are expected to increase company efficiency. The aim of this research is to determine and analyze the restructuring arrangements for companies experiencing financial distress in Indonesian law. To find out and analyze the implementation of mergers at PT. Indosat TBK. with PT. Hutchison 3 Indonesia. And to find out and analyze the legal consequences of the PT merger. Indosat TBK. with PT. Hutchison 3 Indonesia.The method used in this research is normative research, namely descriptive analytical research, which is sourced from secondary data with primary legal materials, secondary legal materials and tertiary legal materials. Data collection was assessed qualitatively with the help of literature research and documentary research. And using a legal approach. Regulations for company restructuring in Indonesian law are regulated in Law Number 40 of 2007 concerning Companies. PT. Indosat TBK. and PT. Hutchison 3 Indonesia carried out a merger to form a Merger Recipient Company. The Merging Companies will be legally dissolved on the Effective Date of Merger as a result of the Business Combination.